Osteosarcoma and causes of death: A report of 1520 deceased patients from the Cooperative Osteosarcoma Study Group (COSS) - Bielack, Stefan S; Blattmann, Claudia; Borkhardt, Arndt; Csóka, Monika; Hassenpflug, Wolf; Kabíčková, Edita; Kager, Leo; Kessler, Thorsten; Kratz, Christian; Kühne, Thomas; Kevric, Matthias; Lehrnbecher, Thomas; et al. (European journal of cancer (Oxford, England, 2022)
PURPOSE: Most aspects of osteosarcoma have been addressed in detail, but there is no comprehensive analysis of deceased patients and causes of death. METHODS: The database of the Cooperative Osteosarcoma Study Group COSS (1980-03/31/2021; 4475 registered high-grade central osteosarcoma patients) was searched deaths from any cause. Affected patients were analyzed for demographic and baseline variables and disease-status at the time of demise. Deaths from causes other than osteosarcoma were analyzed in detail. RESULTS: A total of 1520 deceased patients were identified (median age (range) at osteosarcoma diagnosis 16 (2-78) years; 908 (59.7%) male, 612 (40.3%) female; primary tumor: extremities 1263 (83.1%), trunk 208 (13.7%), craniofacial 47 (3.1%) (site unknown 2); metastases at registration: absent 1.051 (69.1%), present 466 (30.7%) (3 no data). The median time from diagnosis to death was 2.22 (0.08-32.02) years. 1286 (84.6%) patients succumbed to osteosarcoma (370 without achieving complete remission, 488 first, 428 more than one recurrences), 146 (9.6%) to other, 88 (5.8%) to unknown causes. Chemotherapy-related infections (40), secondary malignancies (39), and perioperative complications (19) were among the most frequent potentially treatment-related causes, and high-dose methotrexate (19), doxorubicin (17), and ifosfamide (15) were the drugs most commonly held responsible. Patients with unknown causes of death had an unusually long median follow-up. CONCLUSION: The major cause of death of patients after osteosarcoma is this malignancy, mostly from one of its multiple relapses. However, almost 10% of fatalities are due to other documented causes. Some of these deaths may be preventable with the knowledge gained from comprehensive analyses such as this.
Keywords: osteosarkom; Humans; ifosfamid; nádory kostí; cisplatina; methotrexát; Cisplatin; Child; doxorubicin; Female; Bone Neoplasms; Methotrexate; protokoly protinádorové kombinované chemoterapie; Doxorubicin; Survival; Osteosarcoma; lidé; Ifosfamide; Adult; ženské pohlaví; Male; Adolescent; Antineoplastic Combined Chemotherapy Protocols; Cause of Death; lokální recidiva nádoru; příčina smrti; mužské pohlaví; Neoplasm Recurrence, Local; mladiství